TEMPERATURE VARIATION IN AN A-B BILAYER SYSTEM DURING RADIATION-INDUCED AB COMPOUND LAYER FORMATION (FUDMA JOURNAL OF SCIENCES, 2025)
Metal silicide formation plays a crucial role in microelectronics, particularly in contact and interconnect technologies. Traditional silicide fabrication methods rely on high-temperature annealing, which can lead to undesirable effects such as increased surface roughness and poor electrical contact. An alternative approach is irradiation-assisted silicide formation, which offers advantages such as lower processing temperatures and improved material properties. Understanding the thermal dynamics during irradiation-induced silicide growth is essential for optimizing this process. In this study, we present a mathematical model that describes the temperature dynamics in an A (metal) - B (silicon) bilayer system under the influence of radiation-induced heating during the formation of an AB (metal silicide) compound layer. The model describes heat generation rates within three irradiated A, AB, and B layers, each with distinct material properties. In this work, we used the nickel-silicon bilayer system as a case study. The result from this study shows that the heat generation rate exhibits both linear and parabolic dependencies on layer thickness and temperature change within the nickel silicide layer during radiation-induced heating. Furthermore, the model reveals a significant finding: the temperature obtained in this study for nickel silicide growth under irradiation is lower than its formation temperature under non-irradiation conditions (e.g., conventional heating processes). This result highlights one of the key advantages of employing irradiation techniques over non-irradiation methods. Lastly, the results also show that the thermal vacancy mechanism is not the dominant atomic transport mechanism during the irradiation of the nickel-silicon bilayer system.
Keywords: Heat generation rate; Heat transfer coefficient; Layer thickness; Radiation induced heating; Radiation particle; Temperature change